Building Loyalty in Indonesia 's E-Commerce Giants: The interplay of Service, Trust, and Satisfaction - Satyawan, Nicole Nadya Aurelie; Prayitno, Sentot Basuki (Institute of Accounting Research and Novation (IARN), 2024)
With the tight lockdown regulations and restrictions, the online shopping trend has resurfaced and made its way to the top due to the COVID-19 pandemic, which led to an increase in online shopping users for about 51% in less than a year. While it offers a multitude of advantages, including convenience, vast selection, and competitive pricing, the inherent lack in physical product interaction can lead to negative experiences if expectations are not met. This study aims to investigate the path towards customer loyalty that includes service quality, trust, and customer satisfaction within Indonesia’s e-commerce giants. Tokopedia and Shopee were chosen as the primary focus of this study due to their market dominance that would capture the substantial portion of Indonesia’s e-commerce industry and draw more generalizable conclusions. Additionally, this study also incorporates the five dimensions of SERVQUAL theory, namely reliability, responsiveness, assurance, empathy, and tangibility, which was less investigated in previous research, especially in Indonesia. An online survey method was employed and distributed through social media platforms to collect the data, and a quantitative analysis was then performed using the data collected from 213 valid respondents who are Indonesian citizens, currently residing in Indonesia, and have recent online shopping experiences through both Tokopedia and Shopee. The empirical results offer valuable insights into customer loyalty within the Indonesian e-commerce context. This study reveals that service quality significantly affects trust, both service quality and trust significantly affect customer satisfaction, and satisfaction was also found to significantly affect customer loyalty. The research emphasizes the paramount importance of prioritizing service excellence across all customer touchpoints, which translates into actions such as developing and implementing standardized service protocols, investing in employee training programs that equip staff with exceptional service delivery skills, and actively soliciting customer feedback to identify areas. By understanding the interplay between service quality, trust, satisfaction, and ultimately, customer loyalty, e-commerce businesses in Indonesia can develop effective strategies to not only attract new customers but also cultivate a loyal and dedicated following.